A review on the recent progress, challenges and perspective of layered double hydroxides as promising photocatalysts. Issue 28 (21st June 2016) - Mohapatra, Lagnamayee; Parida, Kulamani
Abstract : The present review article evaluates the effectiveness and special features of LDH/modified LDH on photocatalytic activities. Abstract : Considering the previous work on layered double hydroxides (LDHs) as novel photocatalysts, research on this group of materials has become one of the most exciting subjects of today. LDH has become an important class of layered materials having prospects in photocatalysis, wherein great attention has been paid to the exhaustive aerobic degradation of pollutants, photocatalytic water splitting, and CO2 photo-reduction. The unique structure, uniform distribution of different metal cations in the brucite layer, surface hydroxyl groups, flexible tunability, intercalated anions with interlayer spaces, swelling properties, oxo-bridged linkage, and high chemical stability are some of the important advantages of this group of materials. This article provides an up-to-date review on significant progress in the fabrication of LDH photocatalytic systems aiming at environmental clean-up and energy production, such as degradation of pollutants, photocatalytic H2 generation and photocatalytic CO2 -reduction. This article, after discussing the recent significant progress in the synthesis of different photoactive LDH materials and photocatalytic applications through their structural and electronic properties, considers many typical examples. In particular, recent progress on the emerging strategies of LDH to improve their photocatalytic activity is also presented. Eventually, the future challenges and outlooks for this group of materials are also discussed.